External validation of a new staging system for severe aortic stenosis in a Portuguese cohort. (25th November 2020) - Silva, C; Maltes, S; Freitas, P; Ferreira, A.M; Teles, R.C; Andrade, M.J; Nolasco, T; Guerreiro, S; Abecasis, J.M; Horta, E; Oliveira, A.F; Ribeiras, R; et al.
Abstract: Background: Recently, a new staging system for severe aortic stenosis (AS) based upon the extent of extra-aortic-valve cardiac damage has been developed (Genereux et al. Eur Heart J 2017). The present study aimed to: 1) determine the prevalence of the different stages of extra-aortic valvular cardiac damage and its impact on prognosis in a real-world Portuguese cohort and; 2) evaluate the distribution of aortic valve calcium score (AV-CaSc) and its prognostic value. Methods: Consecutive patients evaluated at a single-centre TAVI-programme between Nov/2015 and Nov/2018 were retrospective selected. The extent of extra-aortic valve cardiac damage was defined by echocardiography as stage 0 (no cardiac damage), stage 1 (left ventricular damage), stage 2 (mitral valve or left atrial damage), stage 3 (tricuspid valve or pulmonary artery vasculature damage) or stage 4 (right ventricular damage). AV-CaSc was estimated routinely at CT-angiography as per TAVI-programme protocol. The primary endpoint was 1-year all-cause mortality after CT-angiography. Survival analysis (Cox-regression hazards model and Kaplan-Meier) was performed. To account for the effect of aortic valve replacement (AVR), this variable entered the Cox-regression model as a time-dependent covariate. Results: A total of 443 patients (mean age 82±7 years, 44% men, median euroSCORE II 4% [IQR 2.4–5.8]) were identified. After Heart Team discussion, 79% (n=349) underwent AVR (TAVI=307; surgical valve repair=42); 9% (n=42) await intervention; 6% (n=25) remain under medical treatment; 4% (n=19) died during the period of evaluation; and 2% (n=8) underwent palliative aortic balloon valvuloplasty. According to the proposed classification, the distribution of patients from stages 0 through 4 was: 0.2% (n=1), 7.5% (n=34), 67.8% (n=306), 14% (n=63), and 10.4% (n=47). Additionally, for each increasing stage of cardiac damage, the burden of AV-CaSc was higher (from stage 1 through 4: 1776 [IQR 1217–2448]; 2448 [1796–3442]; 2448 [1832–3622]; 2960 [1936–4878] units; p for trend = 0.002). All-cause mortality at 1-year was 14% (n=63). Mortality increased alongside with increasing extent of cardiac damage (from stage 0 through 4: 0% [n=0], 6% [n=2], 12% [n=36], 20% [n=12], and 30% [n=13]) – Fig. Multivariable analysis revealed chronic renal disease (HR 1.37 per stage [1.15–1.64], p<0.001), AV-CaSc (HR 1.02 per 100 units [1.01–1.03], p=0.007), AVR (HR 0.46 [0.26–0.81], p=0.007) and stage of cardiac damage (HR 1.54 per stage [1.15–2.05], p=0.004) as independent predictors of 1-year mortality. Conclusion: In a real-world Portuguese cohort of severe AS patients, the extent of cardiac damage was associated with 1-year mortality. AV- CaSc grants additional prognostic information to this classification. Incorporation of this staging system into patient evaluation may be useful in the risk assessment of severe AS. Funding Acknowledgement: Type of funding source: None